Combination of vitamin A and D supplementation for ischemic stroke: effects on interleukin-1ß and clinical outcome - Alfansuri Kadri; Hasan Sjahrir; Rosita Juwita Sembiring; Muhammad Ichwan (Medicinski glasnik, 2020)
Aim: Accumulated evidence suggests that vitamin A and D agonists can alleviate the development of atherosclerosis. Therefore, the aim of this study was to determine the effect of vitamin A and D combination supplement on interleukin-1? (IL-1?) and clinical outcome in ischemic stroke. Methods: A single-blind, randomized controlled trial was conducted on ischemic stroke patients at Adam Malik Hospital between March 2018 to February 2019. The patients were randomized into 4 groups of the treatment consisting of supplementation using vitamin A or D only, combination of vitamin A and D, and placebo group, all given for 12 weeks. Clinical outcome was determined using the National Institute of Health Stroke Scale (NIHSS). At the time of admission and after the treatment was completed, all patients were measured for vitamin A, vitamin D, and IL-1? serum level, and NIHSS score. Results: From the total of 120 patients, in the combination group there were significant increments on both vitamin A (p=0.04) and vitamin D (p=0.01) serum level after 12 weeks of the treatment, compared to the other groups. In conjunction, IL-1? serum level showed a significant decrement in the combination group (p<0.001). Lastly, the biggest improvement of NIHSS could be seen in the combination group, which was marked by the highest decrement of NIHSS score (p<0.001). Conclusion: Administration of combination of vitamin A and D supplementation can significantly increase vitamin A and D serum level, decrease IL-1? serum level, and ultimately improve clinical outcome in ischemic stroke patients.
Keywords: cerebrovascular disorders; cytokines; nutrients; stroke/drug therapy